The Development of German Monologies in the Pandemic Time Based on Short Stories into Prose Anthologies as Teaching Materials of German Literature - Ahmad Bengar Harahap; Hafniati; Indah Aini (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2022)
Monologue is a literary work that is included as a prose study which was created not only to be understood, but more than that monologue must be enjoyed, lived and interpreted. The study of monologue is part of literary learning that can be performed in a stage or performance through the process of show a single drama with various sources as a script, one of which is a short story. During the current phenomenal Covid 19 pandemic, the impact is very significant in affecting all aspects of life, but there are many prose literary works that can be performed by literary actors, including students, in appreciating the pandemic atmosphere. Short stories in German literature can be performed through monologue performances both online and offline as a concept for the study of prose studies during a pandemic. The output can produce an anthology of monologues as an interesting prose literature teaching material to be discussed and investigated in research. Therefore, this study aims to; (1) to develop teaching materials for German literature or literature to improve the skills of German-language students in prose studies, (2) to become learning models or practical learning models in German literature or literature courses. The model used in this study is Model Richey and Klein (2007). From the results of the research, it will be obtained that the German monologue anthology book during the covid19 pandemic time as teaching materials and digital media for learning literary practice and its output also becomes an indexed journal article or proceedings on a national and international scale.